Loka sāhitya vimarśa - Agravāla, Svarṇalatā, 1915- (Ratna Smrti Prakāśana ; vitaraka Campālāla Rānkā, 1979)
Analytical study of the literary and socio-religious perspectives of Rajasthani folk literature.